Pengaruh Komitmen, Dan Kompetensi Terhadap Kinerja Asn Kantor Badan Penghubung Pemda Propinsi Sulawesi Tenggara Di Makassar - Dewi Anggraeni; Rina Rina; Andi Hendra Syam (Jurnal Online Manajemen ELPEI, 2023)
This research wants to obtain a phenomenon about the influence of ASN commitment and competency on ASN performance. This research unit consisted of 31 ASN respondents, the Southeast Sulawesi Provincial Government Liaison Agency Office in Makassar The results of the research and data analysis are in the form of variable descriptions, reliability tests, validity, transformation of ordinal data into interval data, statistical testing with   to determine the effect of commitment and competence of ASN    on ASN  performance partially or simultaneously. Interpretation of the research results includes three parts: the effect of commitment on ASN performance partially by 39.5% is stated to be significant, the effect of ASN competence on ASN performance partially by 51.4% is stated to be significant, while simultaneously the effect of commitment and ASN competence on ASN performance is 34.9% declared significant. While the rest is influenced by other factors outside the model which can be interpreted as influenced by the variables of moral decadence, motivation and leadership style. The conclusion of this study, simultaneously the commitment and competency of ASN  has a significant positive effect of 34.9% on ASN  performance, while the remaining 65.1% is determined by other variables not mentioned in this model, partially commitment has a positive and significant influence on ASN  performance, namely 0.395 and 0.001 < 0.05, partially ASN competency, has a positive and significant influence on ASN performance namely 0.514 and 0.000 < 0.05.